Functional Characterization of a Small-Molecule Inhibitor of the DKK1-LRP6 Interaction. (23rd January 2012) - Iozzi, Sara; Remelli, Rosaria; Lelli, Barbara; Diamanti, Daniela; Pileri, Silvia; Bracci, Luisa; Roncarati, Renza; Caricasole, Andrea; Bernocco, Simonetta
Abstract : Background . DKK1 antagonizes canonical Wnt signalling through high-affinity binding to LRP5/6, an essential component of the Wnt receptor complex responsible for mediating downstream canonical Wnt signalling. DKK1 overexpression is known for its pathological implications in osteoporosis, cancer, and neurodegeneration, suggesting the interaction with LRP5/6 as a potential therapeutic target. Results . We show that the small-molecule NCI8642 can efficiently displace DKK1 from LRP6 and block DKK1 inhibitory activity on canonical Wnt signalling, as shown in binding and cellular assays, respectively. We further characterize NCI8642 binding activity on LRP6 by Surface Plasmon Resonance (SPR) technology. Conclusions . This study demonstrates that the DKK1-LRP6 interaction can be the target of small molecules and unlocks the possibility of new therapeutic tools for diseases associated with DKK1 dysregulation.